Research on Access and Handover Authentication Mechanism of SpaceIntegrated-Ground Information Network for Multi-Type Terminals - Jin CAO; Lilan CHEN; Ruhui MA; Hui LI; Fenghua LI (天地一体化信息网络)
With the maturity of the key technologies of the new spectrum of the network, the network can accommodate users of various frequency bands.In order to make eff ective use of resources, diff erentiated terminals need targeted and customized security protection mechanisms.In the unifi ed network architecture, three access authentication mechanisms were proposed for common terminals, high-speed terminals and Ka terminals.At the same time, in order to ensured that diff erent types of terminals could still obtain continuous network services after accessing the network, a switching authentication mechanism based on pre-switching was proposed to provided unifi ed security switching services for the three types of terminals.Formal verifi cation tool named Scyther and informal security analysis results showed that the proposed scheme meet a variety of security requirements of the proposed scenario.At the same time, compared with the same type schemes, the proposed scheme can achieve the eff ective balance between security and performance, which can meet multidimensional integration of heaven and earth network of the scene terminal access switch and certifi cation requirements.